BIAS GENDER DALAM PEMBERITAAN TIM SEPAKBOLA PEREMPUAN DI CHINA SELAMA JANUARI 2011 â MARET 2012 OLEH MEDIA ONLINE XINHUANET DALAM ANALISIS ISI - , RIZKY DIAH AYU PITALOKA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Xinhua very important role, as the online media with access from 200 countries and regions throughout the country, as well as included in the ranking of 100 online media across the country. Thus, XinHua.net necessarily required to disseminate accurate and objective information for pengaksesnya. This gender bias in the media showed certain ideologies, which ultimately underlies a medium in the process of reporting and preaching. Thus, behind the success of the women who served through the media, there are the interests of men who met, thus showing the women who are not independent in total. Although in a proclamation, presents a woman who is successful, but the success of the show seemed very apparent as the roles of men behind the success.